Content Marketing and Online Reviews: Keys to Purchase Intention for Brodo Products on TikTok Shop - Henny Utarsih; Siti Nur Rani Syadiah (International Journal of Management Science and Information Technology, 2026)
The rapid development of digital technology has transformed marketing strategies, particularly through social commerce platforms such as TikTok Shop. This study examines the effects of content marketing and online customer reviews on consumers' purchase intention toward Brodo products on TikTok Shop. A quantitative survey was conducted with 100 respondents who had viewed Brodo's TikTok marketing content and read customer reviews before making or considering a purchase. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 3.0. The results show that content marketing has a positive and significant effect on purchase intention (β = 0.268; p = 0.010), while online customer reviews have a stronger positive and significant effect (β = 0.545; p < 0.001). The model explains 60.2% of the variance in purchase intention. This study contributes to the digital marketing and social commerce literature by simultaneously comparing the relative influence of company-generated content and consumer-generated reviews in the context of an Indonesian local fashion brand on TikTok Shop. Practically, the findings indicate that brands should combine informative, relevant, and authentic content with credible review management, responsive customer service, and consistent product quality to strengthen consumer trust and purchase intention.